Nuclear energy in the era of climate resilience: advancing long-term scenarios with the world-times model - Fankhauser Doyle Edenhofer; Lehtveer Loulou Parikh; Sen Zhu Wang Yu (Institute of Computer Science (IOCS), 2023)
Sustainable energy routes that improve climate resilience are needed because climate change affects global energy systems. Nuclear energy's low-carbon electricity could mitigate climate change. This study uses the World-TIMES Model to assess its climatic resilience. A mathematical optimization model is used to discover the best energy mix, including nuclear power, to minimize greenhouse gas emissions and meet energy demand and cost limitations. We use a simplified numerical example to demonstrate the concept and assess nuclear energy, renewable sources, and cost-effectiveness trade-offs. Wind and solar electricity are better in the scenario, reducing greenhouse gas emissions and mitigating climate change. This conclusion is scenario-specific, and real-world difficulties demand more thorough models. Thus, the study emphasizes regional-specific data, dynamic dynamics, and sensitivity analysis. This work improves our understanding of nuclear energy's potential in climate-resilient energy systems and aids policymakers in developing evidence-based energy strategies. The report also emphasizes the importance of renewable energy sources in reaching climate targets and urges future research to solve real-world difficulties and maximize nuclear energy integration in long-term energy planning